Firm Size and the Task Content of Jobs: Evidence from 47 Countries - Micole De Vera; Javier Garcia-Brazales (ZBW - Leibniz Information Centre for Economics, 2021)
Using a mix of household- and employer-based survey data from 47 countries, we provide novel evidence that workers in larger firms perform more non-routine analytical and interpersonal tasks, even within narrowly defined occupations. Moreover, workers in larger firms rely more on the use of information and communications technologies (ICT) to perform these tasks. We also document a 17% wage premium that workers in larger firms enjoy relative to their counterparts in smaller firms. We find evidence that the firm size gradient in the task content of jobs accounts for around 10% of the large firm wage premium.
Keywords: J24; J31; L25; 330; Tasks; Occupations; Firm size; Cross-country evidence; Wage differential